Physical and Biological Characterizations of Injectable Thermosensitive Poly(N-Isopropylacrylamide)-Collagen I Hydrogels Intended for Meniscus Repair - Chunhai Ke; Xuanyuan Lu; Jiahua Ni; Ruicong Li; Qi Chen; Zhaoxiang Peng (International Journal of Polymer Science)
There has been an increase in the incidence of meniscus injuries worldwide, as well as growing needs for injectable hydrogels with the potentials to promote in situ meniscal tissue repair. This work developed poly(N-isopropylacrylamide)-collagen I composite hydrogels, with a series of different collagen I contents. The hydrogels were injectable under room temperature and started to solidify around 32°C due to their thermosensitivities, meeting the requirements of the intended applications. The addition of collagen I to the poly(N-isopropylacrylamide) provided physical reinforcement to the hydrogels. Rheological characterizations showed that, under room temperature, the complex viscosity, the storage modulus, and the loss modulus, respectively, increased from 0.71±0.35 Pa•s to 110.95±23.22 Pa•s, from 3.28±2.02 Pa to 658.06±128.07 Pa, and from 3.30±1.01 Pa to 308.78±56.67 Pa, as the collagen I content in the hydrogel increased from 0% to 1%. Cell proliferation tests and high-density culture also revealed that collagen I promoted bioactivity of the hydrogels and induced fibrochondrocyte phenotype of the chondrocytes. The expressions of collagen I protein and collagen I a1 gene in the PNIPAm-0.5Coll group were 3.50-fold and 3.64-fold of those in the PNIPAm group. In contrast, the expressions of collagen II protein and collagen II a1 gene were less prominent (respectively, 2.36-fold and 3.34-fold in the PNIPAm-0.5Coll group compared with the PNIPAm group). This phenotyping was believed to be conducive to the regeneration of meniscal tissues. The findings of this study have provided an important basis for future in vivo studies and clinical applications of this type of composite hydrogels.